Urbanisation affects the diet and feeding selectivity of the invasive guppy Poecilia reticulata. Issue 2 (29th October 2019) - Ganassin, Maria J. M.; Frota, Augusto; Muniz, Carolina M.; Baumgartner, Matheus T.; Hahn, Norma S.
Abstract: The process of urbanisation is increasing the frequency and magnitude of fluctuations in the availability of food resources for fish. In this study, we investigated whether the diet and prey selected by the guppy Poecilia reticulata reflect the different levels of urbanisation using the total area of impervious surface soil as the metric. Rural streams (low percentage of urbanisation—LPU) and urban streams (high percentage of urbanisation—HPU) were sampled during both the rainy and dry seasons. The hypothesis tested was that the diet and selective behaviour differ spatially and seasonally between LPU and HPU streams. Among the analysed items, seasonal significant differences were only observed in HPU streams. In LPU streams, the trophic spectrum was wider, and a higher diversity of prey was selected. In HPU streams, the diet richness was lower with a dominance of Chironomidae, and there was also less variability in selected prey. Ephemeroptera and Trichoptera were always avoided, but Coleoptera were avoided only in LPU, while Oligochaeta were avoided in HPU streams. Thus, the diet and prey selected by P. reticulata were different between LPU and HPU streams, and this species has potential to compete for food with the native fauna in a wide variety of environmental conditions and available resources. Therefore, this dietary flexibility probably offers competitive advantages when colonising and establishing in a new habitat.